The African, Caribbean and European (ACE) Pathways to Care study: a qualitative exploration of similarities and differences between African-origin, Caribbean-origin and European-origin groups in pathways to care for psychosis. Issue 1 (14th January 2015) - Ferrari, Manuela; Flora, Nina; Anderson, Kelly K; Tuck, Andrew; Archie, Suzanne; Kidd, Sean; McKenzie, Kwame
Abstract : Objectives: This paper reports on a qualitative exploration of the reasons for differences in pathways to care and duration of untreated psychosis (DUP) in the African, Caribbean and European (ACE) Pathways to Care study from the perspective of respondents to the study and their families. Setting: Ontario, Canada. Participants: Thirty-four participants in total. Twenty-five young people who had experienced a first episode of psychosis and nine family members. Participants were part of the ACE Pathways to Care study. Design: We implemented six focus groups. Furthermore, we implemented four in-depth interviews with two African-origin young women, one Caribbean-origin woman, and one European-origin woman with lived experience of psychosis. Results: Factors that influenced help-seeking delays across the three groups were: personal awareness of symptoms, family members' knowledge of psychotic symptoms and knowledge of mental health services. Youth and their family members described how stigma played a key role in pathways to care by stopping them from asking for help. The way in which stigma operated on the three groups' members, from feeling ashamed to feeling guilty for their mental illnesses, helped to explain differences in DUP between the groups. Guilt feelings emerged as a prominent theme among members from the African and Caribbean groups and it was not discussed in the European focus group. Delay in entering into first-episode psychosis programmes was also influenced by the stigma perceived by young people in healthcare settings. This had an impact on the therapeutic relationships, disclosure of symptoms and overall trust in the healthcare system. Conclusions: The findings of this paper suggest that stigma, especially internalised stigma, may operate in different ways in European-origin, African-origin and Caribbean-origin groups. These findings could inform the development of more equitable services for people in early stages of psychosis.